Family Meanings in Perunggu's '33X' Music Video: The Study of Semiotic Analysis Roland Barthes - Dharma, I. Komang Oka; Pratami, Febryanti; Sadiyyah, Zulfanida Nurul (Sinergi International Journal of Communication Sciences, 2024)
This research was conducted with the objective of analyzing the representation of the meaning of kinship in the music video of the band Perunggu entitled "33x" through the lens of a qualitative approach to Roland Barthes' semiotic analysis. Music videos can be utilized as a conduit for the dissemination of messages to the audience. The data collection techniques employed in this study are based on documentation studies, with the primary data sources being music videos. The data analysis techniques employed in this research include data reduction, data display, and conclusion drawing.  The analysis leads to the conclusion that kinship can be obtained from simple things. This is demonstrated by several images of scenes captured by the researcher during the research process. The music video represents the meaning of family as a relationship that is not affected by the passage of time. It also represents the enduring bond between a father and son, as evidenced by the father's joy when talking with his son and the father's recollection of his son's childhood through the opening of a photo album.